2008
DOI: 10.1103/physrevlett.100.256801
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Pinning Mode of Stripe Phases of 2D Systems in High Landau Levels

Abstract: We study the radio-frequency diagonal conductivities of the anisotropic stripe phases of higher Landau levels near half-integer fillings. In the hard direction, in which larger dc resistivity occurs, the spectrum exhibits a striking resonance, while in the orthogonal, easy direction, no resonance is discernible. The resonance is interpreted as a pinning mode of the stripe phase.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 32 publications
3
42
1
Order By: Relevance
“…Our recent measurements 26 revealed that the ground state at ν = 5/2 undergoes a pressure-driven quantum phase transition from the FQHS to a stripe phase [27][28][29][30][31][32][33][34][35][36][37] . In this experiment the two-dimensional electron gas was not exposed to an in-plane magnetic field or any other externally applied symmetry breaking fields 26 .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Our recent measurements 26 revealed that the ground state at ν = 5/2 undergoes a pressure-driven quantum phase transition from the FQHS to a stripe phase [27][28][29][30][31][32][33][34][35][36][37] . In this experiment the two-dimensional electron gas was not exposed to an in-plane magnetic field or any other externally applied symmetry breaking fields 26 .…”
mentioning
confidence: 97%
“…This FQHS, similarly to all other FQHSs 3,4 , is topologically ordered, it is believed to belong to the Pfaffian universality class [5][6][7][8][9][10][11][12][13][14][15][16][17] , and it is thought to support non-Abelian excitations 5 . Within the framework of the composite fermion theory 18,19 , the ν = 5/2 FQHS can be understood as being due to pairing of composite fermions, a pairing driven by the residual attractive interactions between the composite fermions 5,20-25 .Our recent measurements 26 revealed that the ground state at ν = 5/2 undergoes a pressure-driven quantum phase transition from the FQHS to a stripe phase [27][28][29][30][31][32][33][34][35][36][37] . In this experiment the two-dimensional electron gas was not exposed to an in-plane magnetic field or any other externally applied symmetry breaking fields 26 .…”
mentioning
confidence: 99%
“…In the same experiment, the stripe period was determined to 3.6 · . Apart from that, pinning mode resonances have been observed as reported earlier for the bubble phase [114,115]. Interestingly, in the case of the stripe phase, a resonance only occurs if the electric field of the microwave signal is oriented along the hard axis.…”
Section: The Stripe Phasementioning
confidence: 58%
“…The temperature dependence of the transport anisotropy at = 9 ⁄2 has been analyzed and was found to be consistent with the predictions of a nematic phase [111,112]. Apart from that, resonances in the microwave absorption have been observed and interpreted as pinning modes of the stripe crystal [114,115]. Yet, with these techniques microscopic details remain elusive.…”
Section: Tilt Induced Phase Transition At = 5 ⁄2mentioning
confidence: 79%
See 1 more Smart Citation